Governance at ICICI Bank chairman’s dilemma - Barua, Samir; Varma, Jayanth R. (London : Indian Institute of Management, Ahmedabad, 2024)
The Board of ICICI Bank met on January 30, 2019, to decide on the action to be taken against the Bank’s former MD & CEO, Chanda Kochhar, in response to an independent investigation report that found her guilty of violation of the Bank’s code of conduct pertaining to conflict of interest. The non-executive Chairman of the Board of Directors of the Bank, Girish Chandra Chaturvedi, had to decide the possible actions the Board may consider against Kochhar. Punitive action against Kochhar would be a reversal of the earlier decision taken by the Board. In addition, it would require specifying the quantum of punishment. Condoning Kochhar could hurt the credibility of the Board and the reputation of the Bank. While evaluating the choices, Chaturvedi had to maintain professional integrity and be fair to the accused (Kochhar). He had to weigh the justifications for the choices he would put before a possibly divided Board.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporate governance -- Case studies